AN OVERVIEW OF DISTRIBUTED FILE SYSTEM (International Journal of Engineering and Computer Science, 2013)
This paper presents a distributed file system that is a client/server -based application that allows clients to access and process data stored on the server as if it were on their own computer. The purpose of a distributed file system (DFS) is to allow users of physically distributed computers to share data and storage resources by using a common file system. It consists of an introduction of DFS, features of DFS, its background, its concepts, design goals and consideration. It also emphasized on Classical file system: Sun network file system and Andrew file system and a brief study of Google file system.